SOUTH AFRICAN GRAPHIC DESIGNERS’ PERCEPTION OF FOSTERING ORIGINALITY IN THEIR OWN DESIGN PROCESS - Chipangula, Endria (The IIE, 2018)
AIM To investigate the extent to which South African graphic designers perceive their own design process as important in fostering originality. BACKGROUND Literature was reviewed in regards to: originality in the definitions and background of the discipline of graphic design and in the graphic design process; in focus on graphic design; originality within graphic design competencies; and elaborated on the demand originality has within the design discipline. REVIEW METHODS Semi-structured interviews and observations were used and analysed. There were three participants who gave consent to be observed and interviewed. Given the time constraints, it was acknowledged that not a lot of subjects would be willing to participate. Therefore, the number of participants had to decrease. CONCLUSION Literature and data findings were quite comparative and argumentative when it came to grasping originality in the design process. Gradually, the need for originality in the design process becomes evident, but, at the same time, certain barriers are perceived as elements that hold back designers from grasping originality in their design process. IMPLICATIONS There were two major implications. Firstly, the time concept affected originality because processes required for originality become distorted in order to keep up with time constraints. Secondly, the study reveals one common trait that requires the need for a thinking or ideation process.
Keywords: Design process; Design; Graphic Design; Originality; Ideation process